AIA, AFTA and domestic private investment: evidence from Malaysia - Tajul Ariffin Masron (Penerbit Universiti Kebangsaan Malaysia, 2012)
The ASEAN Free Trade Area (AFTA) was proposed in 1992 and followed by the introduction of the ASEAN Investment Area (AIA) in 1998. Both are meant to promote regional economic prosperity through improvements in regional trade and investment. Unfortunately, to date, there is no clear sign that either AFTA or the AIA can really trigger regional economic activity and, therefore, spur regional economic development. The main point often neglected in literature concerning the implications of AFTA and AIA on regional economic development is the role and development of domestic private investment (DPI). In other words, AFTA and AIA will only result in positive and sustainable economic impacts on regional economic development if such developments followed or supported by the development of domestic private investment in each ASEAN member country. Hence, this study aims to investigate the implication of AFTA and AIA on Malaysian DPI.